The Role of Human Dignity in Addressing LGBT: Perspectives on Islam, Human Rights, and Maqosidh Sharia - Habibah, Nurul Fitri (Nizham Jurnal Studi Keislaman, 2023)
This study aims to find out how the role of human dignity in responding to LGBT perspectives of Islam, human rights and Maqasidh Sharia. This study used qualitative research. The method of data collection is by using literature studies or literature that uses books and journals. The data analysis technique is sourced from literature studies. The author emphasizes on which references or libraries are related to the author's title to conduct research. lgbt acts are not permissible according to Islam, human rights and Maqasidh Sharia. But we must not judge people who commit deviant acts like lgbt. The need to set aside religious rules first does not mean to justify lgbt actions but it is related to human values or what we can call human dignity. It would be better if we could embrace people who commit these lgbt acts in the hope that they can return to being normal human beings and carry out their sexual orientation accordingly by and large. Keywords: Human Dignity, LGBT, Islam, Human Rights and Maqasidh Sharia Abstrak Penelitian ini berorientasi supaya mengetahui bagaimana peran martabat manusia dalam menyikapi lgbt perspektif islam, ham dan maqosidh Syariah. Adapun penelitian ini menggunakan penelitian kualitatif. Adapun cara pengumpulan datanya dengan menggunakan studi literatur atau kepustakaan yang menggunakan buku dan jurnal. Adapun teknik analisis datanya bersumber dari studi literatur. penulis menekankan pada referensi atau pustaka mana yang terkait dengan judul penulis untuk melakukan penelitian. Tindakan lgbt tidak dibenarkan menurut islam, ham dan maqosidh Syariah. Namun kita tidak boleh menghakimi manusia yang melakukan tindakan menyimpang seperti lgbt ini. perlunya untuk menyampingkan aturan agama terlebih dahulu bukan berarti untuk membenarkan tindakan lgbt tetapi ini berkaitan dengan nilai-nilai kemanusian atau yang bisa kita sebut dengan martabat manusia. Alangkah lebih baiknya jika kita bisa merangkul manusia yang melakukan tindakan lgbt ini dengan harapan supaya bisa kembali menjadi manusia yang normal dan melakukan orientasi seksualnya sesuai pada umumnya. Kata kunci: Martabat Manusia, LGBT, Islam, HAM dan Maqasidh Syariah